AN UNUSUAL CASE OF MASSIVE NEONATAL GOITRE - Bunari, Siti Nor Raudzah; Teik, Teoh Sze (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Congenital hypothyroidism occurs in one out of 3000 live births in Malaysia. Over 95% of the cases have no clinical manifestations at birth. In this peculiar case, we present a patient with massive neonatal goitre with congenital hypothyroidism. CASE An 8-month-old male was diagnosed prenatally to have a neck mass on a detailed scan at 37 weeks. It was reported to be highly vascularised with possible goitre. Maternal biochemical markers showed euthyroid status, but neck ultrasound revealed multinodular goitre. There were no suggestive risk factors for iodine deficiency. Because of the possibility of airway compression, caesarean section was recommended and he was delivered via ex-utero intrapartum treatment (EXIT procedure) at 38 weeks and 4 days. The infant was intubated and ventilated for respiratory distress. Newborn examination showed an anterior neck mass measuring 2 x 2 cm from midline to the left, with otherwise unremarkable systemic examination. Postnatal computed tomography of the neck revealed massive goitre causing airway compression and oesophageal narrowing from the oropharynx until the thoracic inlet. Laboratory studies supported the diagnosis of congenital hypothyroidism (TSH 37.41 μIU/mL) with possible thyroid dyshormogenesis. Treatment was initiated with oral levothyroxine 50 mcg daily. Serial ultrasound imaging showed a gradual reduction with resolved mass effect and airway compression. CONCLUSION Prompt diagnosis and meticulous thyroid replacement therapy led to significant regression of goitre to a more functional size. Rational intervals of clinical and biochemical evaluation are crucial to ensure optimum growth and neurodevelopmental outcomes.